Pengaruh Media Audio Visual Terhadap Ketepatan Teknik Shooting (Free Trhow) Permainan Bola Basket - Badaruddin, Muhammad Azhari; Abduloh, Abduloh; Aminudin, Rizki (Jurnal Porkes, 2022)
Mastery of the basic free throw shooting techniques for students of SMP Negeri 1 Purwasari is still low, so this study aims to examine the influence of audio-visual media on the accuracy of shooting free throws in basketball learning at SMP Negeri 1 Purwasari. The population in this study was 169 students at SMP Negeri 1 Purwasari and the sample for this study was 44 students. Data acquisition in this study refers to the design used, namely the pretest and posttest designs. Data analysis in this study is the normality test, homogeneity test, and hypothesis testing using the IBM SPSS 25 application. The results showed that there was a significant effect of audio-visual media on the accuracy of free shooting. throw on basketball lessons at SMP Negeri 1 Purwasari. The results showed that the effect of audio-visual media on the accuracy of shooting free throws in basketball learning was seen from the pretest results with a mean value of 3.75, a standard deviation value of 1.110 and posttest results with a mean value of 4.295 with a standard deviation value of 1.11. As well as testing the hypothesis with a significant level (0.05) and obtained sig. From testing the hypothesis using the t test where 0.0000 <0.05. It can be concluded that there is an increase in the accuracy of the free throw shooting technique in basketball learning at SMP Negeri 1 Purwasari, then it can be seen from the percentage change in the posttest average score of 3.75 > 4.85 pretest average value.